Mimikri Pribumi dan Kolonial Belanda dalam Novel "Student Hidjo" karya Mas Marco Kartodikromo: Kajian Postkolonialisme: The Mimikriry of The Individual and Colony of The Netherlands in "The Student Hidjo's" Novel Works of Mas Marco Kartodikromo: Postcolonial Studies - Sarifah, Riski Nur; Safitri, Ika Nor (Kibas Cenderawasih, 2023)
This article will describe how the form of mimicry or imitation was done by the natives to the Dutch and the Dutch to the natives in the novel Student Hidjo by Mas Marco Kartodikromo. The purpose of this study was to determine the intrinsic elements and forms of mimicry or imitation of the characters in the novel. The method used is descriptive with a qualitative form. The approach used in this study is a postcolonial approach. Based on the analysis, several forms of mimicry or imitation were found in the Student Hidjo novel, including; mimicry of the use of language, mimicry of equipment for human life, mimicry of customs, and mimicry of science.